6(k-8)+4(-1-3k)=58

Simple and best practice solution for 6(k-8)+4(-1-3k)=58 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(k-8)+4(-1-3k)=58 equation:


Simplifying
6(k + -8) + 4(-1 + -3k) = 58

Reorder the terms:
6(-8 + k) + 4(-1 + -3k) = 58
(-8 * 6 + k * 6) + 4(-1 + -3k) = 58
(-48 + 6k) + 4(-1 + -3k) = 58
-48 + 6k + (-1 * 4 + -3k * 4) = 58
-48 + 6k + (-4 + -12k) = 58

Reorder the terms:
-48 + -4 + 6k + -12k = 58

Combine like terms: -48 + -4 = -52
-52 + 6k + -12k = 58

Combine like terms: 6k + -12k = -6k
-52 + -6k = 58

Solving
-52 + -6k = 58

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '52' to each side of the equation.
-52 + 52 + -6k = 58 + 52

Combine like terms: -52 + 52 = 0
0 + -6k = 58 + 52
-6k = 58 + 52

Combine like terms: 58 + 52 = 110
-6k = 110

Divide each side by '-6'.
k = -18.33333333

Simplifying
k = -18.33333333

See similar equations:

| 10-3x+10x-7=15 | | x+3-2x=5-7x+1b | | 1/4-1/2=-3/4 | | 7-2q1/2n | | 5/6n=-9 | | 7f-24=5 | | P/5-5/P | | x^3-2x^2+kx+14=0 | | 6x+7=7x+14 | | 7=0.9y | | 3-4(4n+4)=49 | | -18=-6+2w | | 0=x^2-6x+0 | | 40a-5= | | 5x+30=2x+140 | | 6n+4-2n=16 | | 5m+7-m+5=28 | | .05+n*9=16 | | 4(59)=76.5 | | 2-3/4w | | B-4/3=b | | 1/2(x-10)=4 | | 2x+3(-12x+8)=-10 | | 5b+6-6b-2=19 | | 30=5w-5 | | Y-1.5=7.5 | | 3-4t+11=-2 | | 5.50x-25=65 | | 7X+8x-4x-5=50 | | 8/12=x/32 | | =2t^2-84t+1025 | | 145x-55=56 |

Equations solver categories